Pengaruh Harga Komoditas Global, Penyertaan Modal Negara, Dan Total Aset Terhadap Pembagian Dividen Bumn Pertambangan Dalam Mendukung Pemerimaan Negara - Dodi Firman Syah; Haryadi; Hodijah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
State-owned enterprises (SOEs) in the mining sector play a strategic role in state revenue, particularly through dividend payments as Non-Tax State Revenue (PNBP). This study aims to examine the effect of global commodity prices, state capital participation (PMN), and total assets on dividend distribution in mining SOEs. The data used is panel data for four mining SOEs (PT Timah, PT Antam, PT Inalum, PT Bukit Asam) for the 2017–2024 period, with a total of 32 observations.The analysis method uses panel data regression, and model selection is carried out using the Chow and Hausman test, which leads to a Fixed Effects Model (FEM). The results indicate that global commodity prices significantly influence dividend distribution (t = 3.518; p = 0.0017), while total assets (t = 1.165; p = 0.2548) and PMN (t = 1.760; p = 0.0905) are partially insignificant.However, simultaneously, all three variables significantly influenced dividends, with an Adjusted R-Square of ± 0.498, indicating the model's ability to explain approximately 49.8% of dividend variation. The findings confirm that state-owned mining company dividends are more sensitive to commodity cycle dynamics, while state-owned mining companies tend to be strategic/episodic, thus delaying their impact on dividends.